Problem-Based Learning (PBL) in Mathematics Learning in Class I SDN 03 Kebak - Tri Kusrini (Universitas Sebelas Maret, 2022)
Mathematics is a subject that must be studied at all levels of education, including the elementary school level. Mathematics learning in elementary schools is used as a basic foundation in building students' mathematical knowledge in critical reasoning. Because of the importance of mathematics in this life, teachers have an important role in increasing students' interest in mathematics. Teachers are also required to design interesting and fun learning activities that make students more enthusiastic about learning. With a high learning enthusiasm will improve the quality of effective learning and of course will achieve the expected goals. Mathematics lessons are often frightening for students because in learning mathematics students are required to think harder to solve a problem. With respect to mathematics subjects are dominated by problem solving so that the Problem Based Learning (PBL) model is suitable for application in mathematics learning.